Marginalization and Underrepresentation in Virtual Exchange: Reasons and Remedies - Alami, Nael; Albuquerque, Josmario; Ashton, Loye; Elwood, James; Ewoodzie, Kwesi; Hauck, Mirjam; Karam, Joanne; Klimanova, Liudmila; Nasr, Ramona; Satar, Müge (Journal of International Students, 2022)
The recent expansion of virtual exchange (VE) in lieu of the Covid-19 pandemic and the ongoing advance of technology has resulted in considerably larger numbers of VE participants for those in certain areas and contexts, yet not all would-be participants have been so fortunate. In some regions and in various contexts, challenges in VE implementation have resulted in disadvantaged populations in terms of underrepresentation and marginalization in global VE networks. To illuminate such challenges, a mixed-method approach was utilized in the current study, beginning with a global survey to elucidate reasons for underrepresentation in terms of political, governmental, institutional, administrative, technological, pedagogical, cultural and personal challenges. Thereafter, semi-structured interviews with instructors, administrators, and educational decision makers were conducted to gain further insights. Although VE is now well established as an impactful mode of studying abroad, various region-specific challenges remain. We conclude with recommendations for underrepresented regions and populations.